Cervical cancer prevention program in Jakarta, Indonesia: See and Treat model in developing country - Nuranna, Laila (Korean Society of Gynecologic Oncology and Colposcopy, 2012)
OBJECTIVE: The purpose of this study was to describe the implementation of single visit approach or See-visual inspection of the cervix with acetic acid (VIA)-and Treat-immediate cryotherapy in the VIA positive cases-model for the cervical cancer prevention in Jakarta, Indonesia. METHODS: An observational study in community setting for See and Treat program was conducted in Jakarta from 2007 until 2010. The program used a proactive and coordinative with VIA and cryotherapy (Proactive-VO) model with comprehensive approach that consists of five pillars 1) area preparation, 2) training, 3) awareness, 4) VIA and cryotherapy, and 5) referral. RESULTS: There were 2,216 people trained, consist of 641 general practitioners, 678 midwives, 610 public health cadres and 287 key people from the society. They were trained for five days followed by refreshing and evaluation program to ensure the quality of the test providers. In total, 22,989 women had been screened. The VIA test-positive rate was 4.21% (970/22,989). In this positive group, immediate cryotherapy was performed in 654 women (67.4%). CONCLUSION: See and Treat program was successfully implemented in Jakarta area. The Proactive-VO model is a promising way to screen and treat precancerous lesions in low resource setting.